Exploring the Dynamics of Faith and Social Integration: A Cross-Institutional Analysis of Religious Moderation Among Students in Medan State University and North Sumatra University - Samosir, Lustani; Sitio, Robert Juni Tua; Naibaho, Frainskoy Rio; Silalahi, Maryska Debora (MUHARRIK: Jurnal Dakwah dan Sosial, 2023)
This research aims to evaluate religious moderation among Medan State University (UNIMED) and North Sumatra University (USU) students in the context of their social life. The method used is a descriptive quantitative method. The population consists of students from the USU Faculty of Cultural Sciences and the UNIMED Faculty of Social Sciences, each around 4,000 people. A 912 sample was determined using the Slovin formula and randomly selected via Googleform distributed by each faculty. Data collection was carried out through closed questionnaires regarding Religious Moderation. Testing the questionnaire on 30 respondents showed the validity of all questionnaire items with a correlation above 0.361 at a confidence level of 0.05. The instrument's reliability was measured using Cronbach's alpha equation with a result of 0.937, indicating an excellent level of reliability. Data analysis was carried out using the average formula. The research results show that the religious moderation of students in North Sumatra is quite good. Questionnaire data from 912 USU and UNIMED students shows that almost all dimensions of religious moderation are in the very high category, with an average score for National Commitment of 4.437%, Tolerance of 4.274%, Non-Violence of 4.441%, and Accommodation to Local Culture of 4.425 %. These results show excellent religious moderation among students at both universities.